Improving community environmental literacy regarding the impact of mercury use in the artisanal small-scale gold mining sector (A study in Sumalata Timur District, North Gorontalo Regency, Gorontalo Province) - Sri Maryati; Fitryane Lihawa; Daud Yusuf; Muhammad Iqbal Liayong Pratama; Muh Kasim; Noviar Akase; Nurmuhniyanti M. Hubaib (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
This research focuses on villages where the community mostly works in the small-scale gold mining sector (ASGM), namely Hulawa Village and Buladu Village, North Gorontalo Regency. Mercury has remained being used by the community in this location for gold processing since a long time. It is important to increase the environmental literacy of the community around the ASGM area considering the dangers of mercury to health and the environment. This study aims to improve the environmental literacy of the community around ASGM regarding the mercury dangers to health and environment. Raising the community environmental literacy is carried out through a mercury dangers awareness campaign by playing videos of mercury dangers, distributing mercury-free gold processing leaflets, resources person explanation concerning mercury impact. Public knowledge about the dangers of mercury before and after the campaign was measured through questions. This study shows that there is a rise in the number of people who understand the dangers of mercury after a mercury awareness campaign. The increase in the number of people who understand the mercury dangers shows that audio-visual and printed media are effectively used to increase public awareness of the dangers of mercury in ASGM areas.